Modern Opera of the Late 20th-Early 21st Centuries: World Trends and Ukrainian Realities - Berehova, Olena; Volkov, Sergii (Journal of History Culture and Art Research, 2020)
The ways of transformation of the opera genre at the new historical stage of its development are traced. The integrative aspects of the interaction of opera with other musical genres and types of art, features of the content, aesthetics, genre and style principles, stylistics of modern opera art are revealed. It was found that the basis of the latest operas are historical and mythological, biblical and fairy-tale, tragic and comic plots, masterpieces of ancient and modern drama, prose, and poetry. A wide panoramic review of operas created in recent decades has shown that among the topics that concern artists today, the most relevant are: the greatness and decline of the spiritual leader, the ephemerality of human life, indifference and coldness of modern society, depressing human loneliness, loss of identity, man's destiny in the world, crime and punishment, repentance for sins committed, carnal passions and violence, decomposition and self-destruction of the individual, idealized love, dreams, memory, the subconscious as ways to escape from absurd reality, and so on. The idea that universal values, which have been developed by mankind for many centuries of its existence, remain relevant for the modern generation, and their conceptualization in the latest artistic practice is associated with updating the canon in the direction of creating new hybrid genres, experiments with performers, instruments, place and time of performances, the use of multi-vector neo-style mixes, compositional and performance techniques, directorial interpretations. The place and role of operas of contemporary Ukrainian composers in the world opera process are determined. On the examples of works by M. Skoryk, A. Zahaykevych, L. Yurina, A. Merkhel, etc., as well as the activities of the creative group “New Opera” (I. Razumeiko - R. Hryhoriv) it is proved that the creative pursuits of Ukrainian artists are in line the latest world trends, testify to the high level of professionalism of the Ukrainian school of composition and performance.